GAMBARAN TINGKAT PENGETAHUAN OBAT ORAL KORTIKOSTEROID DI APOTEK NEW BINTANG ILAHI BUKITTINGGI - Eka Rahmadani; Devahimer Harsep Rosi; Miftahul Jannah (Journal of Science and Clinical Pharmacy Research, 2026)
The use of corticosteroids in the community is still quite high, even though these drugs are classified as strong medicines that should only be used with a doctor's prescription. Insufficient knowledge regarding indications, methods of use, and side effects can pose serious health risks. This study aims to determine the level of patient knowledge regarding the use of corticosteroid drugs and the types of corticosteroid drugs purchased at the New Bintang Ilahi Pharmacy in Bukittinggi. The research method used is descriptive prospective with data collection through questionnaires administered to 85 respondents during June 2025. The research results show that the respondents' level of knowledge regarding corticosteroid use is low, with an average correct score of 56.91%. The distribution of knowledge levels is: poor category 55.3%, sufficient 34.1%, and good 10.6%. The most frequently purchased type of corticosteroid was Dexamethasone 0.5 mg (57.64%), followed by Methylprednisone 4 mg and prednisolone 4 mg (35.29%). The conclusion of this study is that the majority of patients at the New Bintang Ilahi Pharmacy in Bukittinggi have a low level of knowledge regarding the use of corticosteroids, therefore more optimal education and counseling from pharmacy personnel is needed.